Investigation Minimal Mean-Squared-Error Algorithm For MIMO In Terms Of Bit-Error-Rate Communication Networks - Arungla’bi, Rismawaty (Prosiding International conference on Information Technology and Business (ICITB), 2017)
In this research conducted research on method development Multiple Input Multiple Output (MIMO) algorithm to improve transmission data communication. The MIMO has multiple antennas in the transmitter and receiver diversity, which is spatial diversity signals transmit, can be obtained from different locations. MIMO is also a technology used to provide high-speed data services in real time with good performance on multipath fading. By using minimal mean-squared-error algorithm at the receiver and compare its performance in terms of bit-error-rate. It can be seen that the investigation system can be significantly improved the signal quality at the receiver. Keywords : Multiple Input Multiple Output, Minimal Mean-Squared-Error, and Bit-Error-Rate